Pulmonary valve myxoma requiring pulmonary valve replacement: a case report - Sawaka Tanabe; Keita Yano; Tae Mizunaga; Yuko Kawamura; Atsushi Takamori; Narihisa Yamada; Koichi Morioka; Takaaki Koshiji (Surgical Case Reports)
Abstract Background Most cardiac myxomas occur in the atria. Myxomas arising from the heart valves are rare, and there are only a few reports of myxomas arising from the pulmonary valve. Complete resection and prevention of embolization at the time of the first surgery are important to prevent the recurrence of myxomas. Case presentation An 82-year-old female was scheduled to undergo surgery for a fracture of the right femoral neck. The preoperative echocardiography showed a mass in the right ventricular outflow tract. The mass was 36 × 30 mm in size and entered into the pulmonary artery during systole. Cardiac synchronous computed tomography showed a stalked bifurcated mass near the pulmonary valve, which was suspected to be a myxoma. Surgical findings showed a lumen-occupying tumor when the main pulmonary artery was incised. Since the tumor was a single mass with a stalk on the pulmonary valve (right and left pulmonary valve cusps), tumor resection and pulmonary valve replacement (bioprosthetic valve) were performed. A right prosthetic femoral head insertion was performed on postoperative day 36, and the patient was transferred to the hospital on postoperative day 44. However, 1 year later, the patient developed a large myxoma (recurrence) that completely occluded the right pulmonary artery and died of right heart failure. Conclusions We report the case of a patient with a very rare myxoma arising from the pulmonary valve, which was treated with tumor resection and pulmonary valve replacement surgery; however, the patient developed another myxoma 12 months later and this tumor was larger than the primary tumor. The surgical margins were indistinct, and there was a high possibility of residual tumor in the pulmonary artery wall; hence, an extended resection should have been considered. The recurrence of myxoma, in this case, suggests that it is important to completely resect the primary tumor during the first surgery and to prevent intraoperative embolization.